The naughty crow - Hale, Irina (New York : Margaret K. McElderry Books ; New York : Maxwell Macmillan International, 1992)
The adventures and misadventures of a tame pet crow, owned by a family living in czarist Russia.
"First published 1992 by William Heinemann Ltd., London, England"--T.p. verso.
Publisher's Weekly
Booklist
School Library Journal
5.4
K-3
Keywords: Crows -- Fiction; Ukraine -- Fiction; Crows -- Fiction; Ukraine -- Fiction